2008
DOI: 10.1002/lt.21467
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning and intermittent clamping confer protection against ischemic injury in the cirrhotic mouse liver

Abstract: Surgery on cirrhotic livers is fraught with complications, and many surgeons refrain from operating on patients with cirrhosis. Surgical procedures include temporal occlusion of blood flow resulting in ischemia. The mechanisms of protective strategies to prevent ischemic injury in patients with cirrhosis are not fully understood. The aim of this study was to evaluate how the cirrhotic liver tolerates an ischemic insult, whether mechanisms other than those observed in the normal liver are active, and whether in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The mouse models of immune-mediated or CCl 4 -induced chronic hepatitis have been reported previously (10,39), and they are summarized in SI Materials and Methods. Twice a week, all mice from both groups were subjected to clinical examination by a board-certified veterinarian (M.M.…”
Section: Methodsmentioning
confidence: 99%
“…The mouse models of immune-mediated or CCl 4 -induced chronic hepatitis have been reported previously (10,39), and they are summarized in SI Materials and Methods. Twice a week, all mice from both groups were subjected to clinical examination by a board-certified veterinarian (M.M.…”
Section: Methodsmentioning
confidence: 99%
“…Animal model studies have shown IPC to be of benefit in almost any tissue type [7][8][9][10][11][12]. In human trials/ cohort studies, there is evidence of the benefit of IPC in human liver [13,14], lung [15,16] and brain tissue [17,18].…”
Section: Ischaemic Preconditioningmentioning
confidence: 98%
“…1A). 14,19 RIPC was done by clamping the femoral vascular bundle just proximal to its confluence with the femoral nerve as described (Fig. 1B).…”
Section: Animal Surgery and Treatmentmentioning
confidence: 99%